2019
DOI: 10.1111/tpj.14432
|View full text |Cite
|
Sign up to set email alerts
|

An allele of ZmPORB2 encoding a protochlorophyllide oxidoreductase promotes tocopherol accumulation in both leaves and kernels of maize

Abstract: Summary Phytol is one of the key precursors for tocopherol synthesis in plants, however, the underlying mechanisms concerning the accumulation of tocopherol remain poorly understood. In this study, qVE5, a major QTL affecting tocopherol accumulation in maize kernels was identified via a positional cloning approach. qVE5 encodes a protochlorophyllide oxidoreductase (ZmPORB2), which localizes to the chloroplast. Overexpression of ZmPORB2 increased tocopherol content in both leaves and kernels. Candidate gene ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 72 publications
3
20
0
Order By: Relevance
“…The repressed protein abundances of PORB and GGR enzymes lead to lower levels of chlorophyll contents and subsequently caused yellow leaf phenotype in several studies (Kimura et al 2018;Li et al 2019;Buhr et al 2017;Liu et al 2015). On the other hand, overexpression of PORB produces more chlorophyll metabolites in plant leaves (Zhan et al 2019) and overexpression of GGR also generates more contents of chlorophylls in tomato leaves (Liu et al 2015). The chlorophyll contents are reduced in oslil3 mutant that is in accordance with the lower accumulation levels of PORB and GGR protein in this mutant.…”
Section: Discussionmentioning
confidence: 62%
“…The repressed protein abundances of PORB and GGR enzymes lead to lower levels of chlorophyll contents and subsequently caused yellow leaf phenotype in several studies (Kimura et al 2018;Li et al 2019;Buhr et al 2017;Liu et al 2015). On the other hand, overexpression of PORB produces more chlorophyll metabolites in plant leaves (Zhan et al 2019) and overexpression of GGR also generates more contents of chlorophylls in tomato leaves (Liu et al 2015). The chlorophyll contents are reduced in oslil3 mutant that is in accordance with the lower accumulation levels of PORB and GGR protein in this mutant.…”
Section: Discussionmentioning
confidence: 62%
“…The development of next‐generation sequencing technologies and genome editing technology such as clustered regularly interspaced palindromic repeats (CRISPR)/CRISPR‐associated protein 9 (Cas9) strategy (Chen et al, 2019) have largely accelerated crop genetic improvement. Efforts have been done to elevate crop yield by knocking out repressors, such as grain number ( OsGn1a) , grain size ( OsGS3 ), grain weight ( OsGW5 , TaGW2 ), panicle size ( OsDEP1 ), and tiller number ( OsAAP3 ) (Li et al, 2016a; Liu et al, 2017; Lu et al, 2018; Zhang et al, 2018), and to enhance plant resistance to biotic stresses, such as powdery mildew in wheat and tomato (Wang et al, 2014; Nekrasov et al, 2017), and blast (Wang et al, 2016) and bacterial blight (Zhou et al, 2015) in rice. In addition, CRISPR/Cas9 has been used to improve quality of crops, such as rice with high‐amylose and resistant starch (Sun et al, 2017), Camelina sativa (Jiang et al, 2017; Morineau et al, 2017) and Brassica napus (Okuzaki et al, 2018) with high oleic acid oil, tomato with enhanced lycopene (Li et al, 2018d) or γ‐aminobutyric acid (GABA) content (Nonaka et al, 2017; Li et al, 2018b), and potato (hairy roots) with less toxic steroidal glycoalkaloids (Nakayasu et al, 2018).…”
Section: Application Of Vitamins In Crop Breedingmentioning
confidence: 99%
“…An alternative pathway of phosphorylation of free phytol to (phytyl-P) and phytyl-PP has been described (Ischebeck et al, 2006;Valentin et al, 2006). Free phytol derives from chlorophyll degradation (Schelbert et al, 2009;Zhan et al, 2019). Afterward, kinases phosphorylate phytol to phytyl monophosphate and phytyl-PP.…”
Section: Synthesis Of Vitamins In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…As well as those in tocopherol biosynthesis pathways, novel genes also exhibit an association with contents of γ-Toc, δ-Toc, and total Toc, including two genes for protochlorophyllide reductase in chlorophyll biosynthesis and a gene for long-chain acyl-coenzyme A synthase in the fatty acid pathway of maize [40, 41]. Recently, a candidate gene association analysis showed that a 5/8-bp insertion/deletion in promoter region of ZmPORB2 encoding a protochlorophyllide oxidoreductase is related to total tocopherol content in maize [50].…”
Section: Discussionmentioning
confidence: 99%